2022
DOI: 10.1161/jaha.121.024385
|View full text |Cite
|
Sign up to set email alerts
|

Health‐Related Quality of Life in Older Patients With Advanced Heart Failure: Findings From the SUSTAIN‐IT Study

Abstract: Background There is a paucity of research describing health‐related quality of life (HRQOL) in older adults considered for advanced heart failure surgical therapies. Using data from our SUSTAIN‐IT (Sustaining Quality of Life of the Aged: Heart Transplant or Mechanical Support) study, we aimed to compare HRQOL among 3 groups of older (60–80 years) patients with heart failure before heart transplantation (HT) or long‐term mechanical circulatory support (MCS) and identify factors associated with HRQOL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…The same was true for many data on baseline patient characteristics and outcome parameters. Many studies from our analysis did not include or report data on patient’s functional heart failure status (e.g., NYHA class) or LV function although these factors already have been proven extensively to have a large impact on quality of life [ 79 , 80 ]. However, many of the included trials either showed data on medical outcome (improvement of functional NYHA class, improvement of measured LV function) or parameters of psychological well-being (quality of life, mental diseases).…”
Section: Discussionmentioning
confidence: 99%
“…The same was true for many data on baseline patient characteristics and outcome parameters. Many studies from our analysis did not include or report data on patient’s functional heart failure status (e.g., NYHA class) or LV function although these factors already have been proven extensively to have a large impact on quality of life [ 79 , 80 ]. However, many of the included trials either showed data on medical outcome (improvement of functional NYHA class, improvement of measured LV function) or parameters of psychological well-being (quality of life, mental diseases).…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for not approaching patients included being too sick, timing of surgery, administrative reasons (eg, staffing issues), and other reasons. 26 Of 393 eligible enrollees, those who underwent surgery and had complete data at baseline, 3 months, or 6 months for either of the 2 outcomes (EQ-5D VAS or KCCQ-12) comprised the sample for this report (n=305): 68 HT MCS, 93 HT non-MCS, and 144 long-term MCS. Reasons for not undergoing HT or long-term MCS implant are listed in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Our data were from the SUSTAIN-IT study (Sustaining Quality of Life of the Aged: Heart Transplant or Mechanical Support). 26 Dr Andrei had full access to all data in the study and takes responsibility for its integrity and data analysis. For this report, we used a prospective, longitudinal, multi-site, observational design.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional inclusion and exclusion criteria have been previously described. 27 Caregivers were approached after patients were enrolled, before implantation of long-term MCS or while awaiting HT. Caregivers were included if they were identified by the patient as the primary caregiver (ie, an unpaid family member or friend who helps the patient with self-care), age ≥21 years, able to speak, read, and write English, willing to participate, and able to provide informed consent.…”
Section: Sites and Samplementioning
confidence: 99%